Temporary Contracts and Employee Effort - Axel Engellandt; Regina T. Riphahn (Institute for the Study of Labor (IZA), 2003)
Temporary contracts provide employers with a tool to screen potential new employees and have been shown to provide "stepping stones" into permanent employment for workers. For both reasons workers on temporary contracts have an incentive to provide more effort than permanent employees. Using indicators for unpaid overtime work and absences taken from the Swiss Labor Force Survey we present evidence that temporary workers indeed provide higher effort than permanent employees: Their probability of working unpaid overtime exceeds that of permanently employed workers by 60 percent. We show the heterogeneity of this effect across different types of temporary contracts, investigate differences between men and women, and discuss the relevance of adverse selection into temporary employment.
Keywords: C25; M50; J41; J24; 330; temporary work; contract-based incentives; absenteeism; overtime; moral hazard; career concerns; Leiharbeit; Befristeter Arbeitsvertrag; Leistungsmotivation; Überstunden; Arbeitsverhältnis; Vergleich; Schätzung; Schweiz